2007
DOI: 10.1097/gme.0b013e318148b28b
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairments with adjuvant anastrozole versus tamoxifen in women with early-stage breast cancer

Abstract: Objective: Hormones have been implicated as modulators of cognitive functioning. For instance, results of our previous work in women with breast cancer showed that cognitive impairment was more severe and involved more memory domains in those who received adjuvant tamoxifen therapy compared with women who received chemotherapy alone or no adjuvant therapy. Recently aromatase inhibitors such as anastrozole have been used in lieu of tamoxifen for the adjuvant treatment of postmenopausal women with hormone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 17 publications
4
111
2
6
Order By: Relevance
“…A more recent study was conducted to compare memory impairment seen with adjuvant anastrozole versus tamoxifen for women with early-stage breast cancer (Bender, et al, 2007). Due to evidence to support lower serum estradiol levels with aromatase inhibition compared to selective estrogen receptor modulation, Bender Additional work related to the impact of menopausal symptoms and fatigue to cognitive function was conducted by Tchen, et al (2003).…”
Section: Evidence For Crci In Breast Cancermentioning
confidence: 99%
“…A more recent study was conducted to compare memory impairment seen with adjuvant anastrozole versus tamoxifen for women with early-stage breast cancer (Bender, et al, 2007). Due to evidence to support lower serum estradiol levels with aromatase inhibition compared to selective estrogen receptor modulation, Bender Additional work related to the impact of menopausal symptoms and fatigue to cognitive function was conducted by Tchen, et al (2003).…”
Section: Evidence For Crci In Breast Cancermentioning
confidence: 99%
“…Furthermore, the results of a substudy of the ATAC study demonstrated that the anastrozole group had worse verbal memory [21]. In another study, Bender et al [22] evaluated the cognitive functions in patients treated with ET for at least 3 months. Memory as well as verbal and visual learning were poorer with anastrozole in comparison to tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what percentage of the subjects had exposure only to tamoxifen, and not to the AI agent. Bender and colleagues [23] studied 31 postmenopausal women aged 21 to 65, and compared anastrozole recipients to tamoxifen recipients. Some of the women in each group had received cytotoxic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%